POSSIBILITIES OF ENSURING PERSONAL FREEDOM AND PUBLIC SECURITY IN CONTEMPORARY MIGRATION CONTEXT: THEORETICAL ASPECT - Aukštuolytė, Nijolė; Stepanovienė, Aušra (Border Security and Management, 2018)
The article deals with compatibility of personal freedom and public security. The aim of the research is to analyse theoretical aspects of the correlation between personal freedom and public security and evaluate their assurance possibilities in the context of contemporary global migration. The article emphasizes value of freedom and security, their interconnection as well as demand and possibilities of their compatibility. Aspects of freedom as personal decision-making and freedom as realizing that decision are analyzed by revealing that extension of freedom boundaries common to contemporary society can turn into self-will with regard to other individuals or society. Such concept of freedom subsequently raises the issue of public security. The following research methods were employed: text interpretation, rational reconstructions, historical explications. On the basis of the methods, the essential ideas of the issue under discussion, its arguments and meanings within historical context were revealed. The conducted analysis allows one to make a conclusion that an individual is free in the society as much as he acknowledges others’ right for freedom whereas the society is secure if certain individual’s self-will is limited for the sake of all society members’ right to freedom. Assurance of personal freedom and public security is the goal of contemporary democratic society and different state institutions including the State Border Guard Service, and has become extremely relevant in the context of modern global migration.